Glycoprotein IIb/IIIa inhibitor use in patients with acute myocardial infarction undergoing PCI: Insights from the TRANSLATE ACS study. Issue 4 (23rd September 2018) - Ibrahim, Homam; Kaltenbach, Lisa A.; Hess, Connie N.; Recchia, Tammy; Effron, Mark B.; Stone, Gregg W.; Wang, Tracy Y.
Abstract: Introduction: Concomitant use of glycoprotein IIb/IIIa inhibitors (GPI) and P2Y12 inhibitors increases bleeding risk. How GPIs are being used with faster onset, higher potency P2Y12 inhibitors are unclear. Methods and results: We studied 11, 781 myocardial infarction (MI) patients treated with percutaneous coronary intervention (PCI) at 233 hospitals in the TRANSLATE ACS study (2010–2012). We used propensity matching to compare 6‐week major adverse cardiac events (MACE: death, recurrent MI, stroke, or unplanned revascularization) and BARC 2+ bleeding events between patients who did and did not receive planned GPI. Planned and bailout GPI were used in 4, 983 (42.2%) and 229 (4.4%) MI patients undergoing PCI, respectively. Patients receiving planned GPI were younger (58 vs. 61 years), more likely to present with STEMI (62.6% vs. 45.4%) or have stent thrombosis (4.2% vs. 2.1%, all P < 0.001) than those without planned GPI use. Planned GPI was used less often with prasugrel/ticagrelor versus clopidogrel (37.1% vs. 43.3%), or when any P2Y12 inhibitor was given >6 hr prior to PCI versus earlier (27.8% vs. 44.4%, both P < 0.01). After propensity matching, planned GPI use was not associated with any difference in MACE (6.4% vs. 5.5% OR 1.18; 95% CI: 0.99–1.57), however, the risk of BARC 2+ bleeding was higher in patients who received planned GPI (11.3% vs. 8.7%; OR 1.34; 95% CI: 1.13–1.59). Conclusion: Planned GPI use as reported by practicing physicians was prevalent between 2010 and 2012 and was associated with increased risk of bleeding but not lower MACE.